Gartland Type III Supracondylar Fractures in Children; Percutaneous Fixation with Two Kirschner Wires from Lateral Side (Journal of Pakistan Orthopaedic Association, 2023)
Objectives: To determine the outcome of percutaneous stabilization of two Kirschner wires from the lateral side in pediatric supracondylar fracture of the humerus.Methods: We conducted this study in the Department of orthopedics, Mardan Medical Complex, from 1st January 2021 to 30th December 2021. After ethical committee approval and informed consent from parents, consecutive patients with type III supracondylar fractures were selected for close reduction and percutaneous pinning (CRPP) from the lateral side. A total of 41 patients including 34 male and 7 female were included in the study. Patients in the age group of less than 15 with Gartland type III supracondylar fractures were meeting the inclusion criteria underwent close reduction and percutaneous fixation (CRPF) with k-wires done from the lateral side only under an image intensifier. Open fractures failed close reduction, polytrauma patients, and vascular injury were excluded. Postoperative results were assessed according to Flynn's criteria.Results: All 41 patients with type III supracondylar fractures were reduced and closely underwent CRPP from the lateral side with a male to female ratio of 4.8:1. Mean age at the time of injury was 7.56 years (range of 4-15). Most of them had an injury on the left side (56.1%) with extension-type fractures being the most common (94.7%). The mechanism of injury was ground-level fall in the majority of cases. Functional results were 70.2% excellent, 19.3 % good, 7.9% fair and 2.6% poor while on the other side cosmetic results were 70.2% excellent, 20.2 % good, 7% fair and 2.6% poor according to the Flynn criteria.Conclusion: K-wire fixation and removal are easier from the lateral side than from the medial or both medial and lateral with the least chances of ulnar nerve injury. The medial epicondyle wire is close to the ulnar nerve and is at risk for injury during fixation and removal of k.wire. It is an effective method of supracondylar fracture fixation in children. It is an alternative to cross-k wire fixation from both the medial and lateral side.